2020
DOI: 10.2478/bog-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do floods affect food security? A before-and-after comparative study of flood-affected households’ food security status in South-Eastern Nigeria

Abstract: A comparative study of pre- and post-flood households’ food security statuses in South-Eastern Nigeria was performed to answer the question “Do floods affect food security?” Data were generated via a survey of 400 households in eight communities using stratified and random sampling methods. Households’ food security statuses were assessed using the Household Food Security Survey Module (HFSSM) and computed using a Rasch analysis, where households were divided into four categories, namely: food secure, food ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
(17 reference statements)
2
20
0
Order By: Relevance
“…Extreme precipitation and related flooding events have both economic and human consequences which have rapidly increased over the years (Kaspersen et al, 2017). Akukwe et al (2020) asserted that flooding has the capability to make communities food insecurity hotspots and thus hamper the achievement of Goal 2 of the Sustainable Development Goals. In Nigeria, floods are the most frequent and severe natural hazards which have significantly affected lives and properties negatively (Olorunfemi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extreme precipitation and related flooding events have both economic and human consequences which have rapidly increased over the years (Kaspersen et al, 2017). Akukwe et al (2020) asserted that flooding has the capability to make communities food insecurity hotspots and thus hamper the achievement of Goal 2 of the Sustainable Development Goals. In Nigeria, floods are the most frequent and severe natural hazards which have significantly affected lives and properties negatively (Olorunfemi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Flooding is one of the most destructive widespread natural hazards of the world with a high frequency of occurrence and a huge impact on large population ( Akukwe et al., 2020 ; Zhao and Gao, 2016 ). It is a major threat to the survival of the human race with associated risks that include the destruction of lives and properties, the displacement of livelihoods, and the impoverishment of flood victims ( Okafor, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas average temperatures are highest in the tropics, the temperate, and polar regions have lower temperatures. Consequently, the negative impacts of climate change are worse in economically vulnerable countries than the strong economies (Akukwe et al, 2020). The impacts of floods, droughts, cyclones, tsunamis, and storms due to climate change, are more predominant in tropics than in temperate regions.…”
Section: Climate Change Flood Disasters and Food Security Nexus Conceptsmentioning
confidence: 99%
“…Ola (2018) focused on the challenges of climate change of rural dwellers of Esanland in Nigeria and concludes that farmers are vulnerable to the adverse impacts of climate change. With more specific emphasis on floods, Akukwe et al (2020) studied flooding as climate change hazard and its impacts on food security in southeast Nigeria. Results of their research confirmed that floods negatively affect food security by increasing the number of food insecure households in the study area.…”
Section: Introductionmentioning
confidence: 99%